Protective effects of cannabidiol on cuprizone-induced demyelination in C57BL/6 mice - Maryam Sajjadian; Iraj Ragerdi Kashani; Parichehr Pasbakhsh; Mahmoud Hassani; Ameneh Omidi; Nasrin Takzare; Tim Clarner; Cordian Beyer; Adib Zendedel (Journal of Contemporary Medical Sciences, 2017)
Objective Experimental and clinical studies suggest that oxidative stress plays an important role in the pathogenesis of multiple sclerosis. In this study, we have investigated the effects of the non-psychoactive cannabinoid cannabidiol (CBD), which exerts antioxidant effects and has recently been approved for the treatment of inflammation, pain, and spasticity associated with MS patients and in a MS mouse model, i.e. cuprizone-induced demyelination. Methods Adult male BL/6 mice were fed with 0.2% cuprizone for 5 weeks, which caused severe demyelination of the corpus callosum (CC). Animals were simultaneously treated with 5 mg·kg−1 CBD by daily intra-peritoneal injections. Using immunohistochemistry and transmission electron microscope, we evaluated the effects of CBD on demyelination, malondialdehyde levels and the activity of reduced glutathione, catalase and superoxide dismutase was evaluated by Biochemical analysis. Results CBD ameliorate the cuprizone-induced demyelination and microglia accumulation. Biochemical analysis showed that oxidative stress induced by cuprizone was reduced by CBD. Conclusion Our data implicate that CBD attenuates destructive cuprizone effects in the CC by decreasing oxidative stress and as well microglia repletion. Keywords cannabidiol, demyelination, oxidative stress, microglia, cuprizone